1990
DOI: 10.1111/j.1600-0897.1990.tb01026.x
|View full text |Cite
|
Sign up to set email alerts
|

Paternal Mononuclear Cell Immunization Therapy for Repeated Miscarriage: Predictive Variables for Pregnancy Success

Abstract: Pregnancy outcomes for 125 women with unexplained recurrent abortion conceiving after immunologic testing for possible paternal leukocyte immunization were analyzed. Pregnancy success was related to the number of previous miscarriages (relative risk 0.36 for each additional miscarriage after 3), a history of a late pregnancy loss (relative risk 0.18), any other relevant treated or untreatable diagnosis (relative risk 0.27), immunization with paternal mononuclear cells (relative risk 5.6), and time in weeks fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
1
1

Year Published

1992
1992
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 9 publications
3
19
1
1
Order By: Relevance
“…Our study has confirmed the findings of Cowchock et al 14 in that there was no correlation between subsequent successful pregnancy and a) degree ofHLA sharing, b) presence of anti-paternal antibody, and c) primary versus secondary aborters. Our study has confirmed the findings of Cowchock et al 14 in that there was no correlation between subsequent successful pregnancy and a) degree ofHLA sharing, b) presence of anti-paternal antibody, and c) primary versus secondary aborters.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our study has confirmed the findings of Cowchock et al 14 in that there was no correlation between subsequent successful pregnancy and a) degree ofHLA sharing, b) presence of anti-paternal antibody, and c) primary versus secondary aborters. Our study has confirmed the findings of Cowchock et al 14 in that there was no correlation between subsequent successful pregnancy and a) degree ofHLA sharing, b) presence of anti-paternal antibody, and c) primary versus secondary aborters.…”
Section: Discussionsupporting
confidence: 92%
“…and Cowchock et al 14 All these studies have shown a success rate of about 70% with immunization and less than 40% in those who are not immunized. In the only double-blind control study reported to date.!"…”
Section: Discussionmentioning
confidence: 96%
“…P1A1 antigen and sensitization to P1A1 could be the main causes of neonatal alloimmune thrombocytopenia, and this group concluded that immunization with mononuclear cells from the PlA1-positive paternal donor possibly leads to neonatal alloimmune thrombocytopenia. 152 There are other potential risks for leukocyte immunotherapy such as enhancing autoimmune diseases, 123 anaphylaxis, serum sickness, abnormal neonates, and Gestosis, but up to now, no single report has been submitted regarding these disorders. They postulated that increased transplacental perfusion of maternal anti-HLA antibodies following allogenic leukocytes immunizations caused this problem.…”
Section: Possible Side Effects Of Litmentioning
confidence: 99%
“…IO ,1l,13,14,16,18 In the present study we have assessed the sera of healthy pregnant women and of non-transfused RSA patients, in order to determine whether this factor is essential to the development of a normal pregriancy and to investigate whether its absence could be considered a relevant parameter for the diagnosis and therapeutic orientation of RSA patients.…”
Section: Methodsmentioning
confidence: 99%
“…10, [14][15][16] We reasoned that if this factor is biologicalIy important for the development of a successful pregnancy, it should regularly be detected in the serum from pregnant women. The present data show that this is not the case, since the inhibitory factor was detected in only 1 out of 13 primigravidae, alI of whom have already delivered a healthy baby.…”
Section: Patientsmentioning
confidence: 99%